Immediate effect of CPAP titration on perceived health related quality of life: a prospective observational study. Issue 1 (December 2016) - Iacono Isidoro, Serena; Salvaggio, Adriana; Lo Bue, Anna; Romano, Salvatore; Marrone, Oreste; Insalaco, Giuseppe
Abstract Background Perceived Health Related Quality of Life (HRQoL) is impaired in obstructive sleep apnea (OSA). This study examines changes in HRQoL aspects occurring immediately after CPAP titration. Furthermore, we analyzed variations in each gender and in patients undergoing home or laboratory-based CPAP titration pathways. Methods Twohundredfive outpatients (151 M) (56.7 ± 10.3 years) were evaluated, before first visit and nocturnal diagnostic examination (T0), and the morning after CPAP titration (T1). Two self-reported HRQoL questionnaires were administered: Psychological General Well-Being Index (PGWBI), composed by six subscales, and 12-Item Short-Form Health Survey (SF-12), including Physical (PCS) and Mental Component Summaries (MCS). CPAP titration was performed using auto-adjusting CPAP units at patients' home or in the sleep laboratory. Results PGWBI scores at T1 improved compared to T0 (p < 0.0001). A similar improvement was observed in SF-12 MCS (p = 0.0011), but not in SF-12 PCS. Changes were independent from anthropometric parameters, OSA severity and excessive daytime sleepiness. Gender comparisons showed better HRQoL in males at both times. At T0, patients who received home or laboratory CPAP titration pathways did not show any differences in PGWBI and SF-12 scores. At T1, PGWBI and SF-12 MCS improved in both home and laboratory groups. Conclusions This study gives evidence that first time CPAP application for titration can lead to a general increase in perceived well-being. Gender comparisons showed better perceived HRQoL with more subscales improvements in males after CPAP titration. The improvement was similar with both home and laboratory CPAP titration pathways.